Simone Weil : Attention to the Real - Chenavier, Robert (Book collections on Project MUSE., 2012)
"How can we articulate the intimate demand of the spiritual life and the struggle for solidarity? These two issues have often been treated separately; in Simone Weil: Attention to the Real, however, Robert Chenavier explores the work of Simone Weil (1909{u2013}1943) and demonstrates how she brought them together in a single movement of thought. "Our time has a unique mission, calling for the creation of a civilization based on the spirituality of work," she wrote near the end of her short life. Her experience as a militant and the call of the divine nurtured in her writing an intense and unwavering defense of this new civilization, backed by her personal sense of intellectual, moral, and political responsibility. Originally published in French in 2009, Simone Weil: Attention to the Real leads the reader through her earliest writing as a perceptive social critic to her work on spirituality and materialism, and finally to her extraordinary concept of decreation, produced before her death at the age of thirty-four. "To an exceptional degree," Chenavier says, "the life of Simone Weil, her personality, her commitment, and her reflection form one single whole." Chenavier argues that Weil's vocation took on a very original form in the history of philosophical thought. He is especially concerned with Weil's philosophical writings on the concept of work, which remain relevant today, and which provide an important key to her thinking throughout her life. Bernard Doering's superb translation brings to English readers Chenavier's succinct account of Simone Weil's life and an illuminating introduction to her philosophical thought."--Publisher's description.